Telephone-supported acceptance and commitment bibliotherapy for people with multiple sclerosis and psychological distress: a randomised controlled feasibility study - Proctor, Barnaby Justin (2016)
Objective: Telephone-supported self-help Acceptance and Commitment Therapy (ACT) may be a way of providing accessible and effective psychotherapy to people with Multiple Sclerosis (MS). The aim of this trial was to determine the feasibility of a randomised controlled trial (RCT) of telephone-supported ACT bibliotherapy compared to treatment-as-usual (TAU), explore the effectiveness of the intervention and track individual changes.